TRUNK BALANCE EXERCISE LEBIH BAIK DARI PADA STRENGTHENING BACK EXERCISE DALAM MENINGKATKAN KESEIMBANGAN KINERJA OTOT ERECTOR SPINE PADA PEMAIN FUTSAL PEMULA - Yusuf Nasirudin; Dewa Putu Gde Purwa Samatra; Wahyuddin -; Susy Purnawati; Ni Made Linawati; Sugijanto - (Sport and Fitness Journal, 2017)
In the game of futsal, work of postural muscle balance needed to maintain the stability of the body for receiving the pass and put the ball into the other team's goal at the time of attack, changing the direction of movement quickly when returning to their respective positions and avoid of back disorder. This research is a form of experimental research that will test the effectiveness of the provision of trunk balance exercise is better than the strengthening of back exercises to improve muscle work balance of erector spine on futsal beginner players, in this study sample will be divided into two groups, the first group will be given trunk balance exercise to improve balance of erectorspine muscles work in futsal begginer players, the second group will be given back strengthening exercise to improve balance of erectorspine muscles work in futsal begginer players.This study was conducted for 6 weeks and the intervention performed 18 times during the study period. Samples measured by surface electromyography to measure work of right and left erector muscle by calculating the proportion of the work on the muscle, the measurement is performed at before the intervention and then intervention in accordance with the grouping which has been divided and then after completion of the intervention, the samples will be re-measured to obtain the value of the intervention.The results of the first group who has been given of trunk balance exercise shows the average value of the before treatment (83.82 ± 2.94) % and the mean value of the after treatment (96.74 ± 2.39) %, and in the second group who has been given strengthening back exercise shows the mean value of the before treatment (88.29 ± 1.89) % and the mean value after treatment (95.91 ± 1.75) %, with the probability value of both groups is 0.000 (p <0.05), and can be expressed there is a significant difference between both groups. In the fourth hypothesis test conducted comparative results of both groups, using independent samples t-test using mean value of the first and second groups, in the first group (12.92 ± 2.94) %, and the second group (7.61 ± 2.12) %, with a probability value 0.000 (p<0.05) and can be expressed in statistical analysis is no significant difference between both treatments were carried out and that means, giving trunk balance exercise is better than back strengthening exercise to improve balance of erector spine muscles work on futsal beginner players.